Strategi Komunikasi Pemasaran Kedai Hegar Coffee & Liwet Melalui Akun Instagram - Ali Alamsyah Kusumadinata; Aditya Ramadhan; Dendi Maulana; Fajar Wiratama (Universitas Mataram, 2023)
Business growth in the Food & Beverage sector presents a great opportunity for entrepreneurs in the culinary space to create new markets. This cafÃ© culinary business is very tempting because of its wide target market from various circles. The emergence of New Media or the Internet today has been considered as a major need in modern companies, it aims to carry out marketing promotion activities. The advancement of technology makes business people take advantage of a form of advertising known as buying and selling